2007
DOI: 10.1098/rsta.2007.2068
|View full text |Cite
|
Sign up to set email alerts
|

Ensembles and probabilities: a new era in the prediction of climate change

Abstract: Predictions of future climate are of central importance in determining actions to adapt to the impacts of climate change and in formulating targets to reduce emissions of greenhouse gases. In the absence of analogues of the future, physically based numerical climate models must be used to make predictions. New approaches are under development to deal with a number of sources of uncertainty that arise in the prediction process. This paper introduces some of the concepts and issues in these new approaches, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(116 citation statements)
references
References 13 publications
0
113
0
3
Order By: Relevance
“…[2] In recent years there has been a concerted effort in the climate modeling community to understand and quantify the uncertainty in future climate projections [Collins, 2007], leading to probabilistic projections of temperature and precipitation that are more informative for decision making than any single model realization [Collins et al, 2006;Murphy et al, 2004]. Probability density functions (PDFs) are often formed by carrying out a sensitivity analysis [Saltelli et al, 2000a].…”
Section: Parameter Screeningmentioning
confidence: 99%
“…[2] In recent years there has been a concerted effort in the climate modeling community to understand and quantify the uncertainty in future climate projections [Collins, 2007], leading to probabilistic projections of temperature and precipitation that are more informative for decision making than any single model realization [Collins et al, 2006;Murphy et al, 2004]. Probability density functions (PDFs) are often formed by carrying out a sensitivity analysis [Saltelli et al, 2000a].…”
Section: Parameter Screeningmentioning
confidence: 99%
“…Hawkins and Sutton (2009) showed that towards the end of the twenty-first century, the RCPs are the dominant source of uncertainty in climate projections. In regard of the climate models, also the choice of GCM and RCM can have a large impact on the results and generally an ensemble of projectionsencompassing different GCMs, RCMs and emission scenarios -is recommended in hydrological climate change impact assessment (Hewitt and Griggs 2004;Collins 2007). A clear distinction on the relative effects of hydrological model (HM) uncertainty and climate model (CM) uncertainty to the projected discharge uncertainty has not been concluded; results vary between studies depending on catchment climate and hydrological variable studied (Hagemann et al 2013;Velázquez et al 2013;Vetter et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In landslide susceptibility assessment this can be considered as an unresolved problem [46][47][48] in [41]. In other disciplines, for example meteorology, a long experience in combining multiple model forecasts already exist [49]. Exploiting ensemble analysis to obtain the most probable forecast is a common practice [41].…”
Section: Resultsmentioning
confidence: 99%